PERTIMBANGAN PASAR KERJA, PENGAKUAN PROFESIONAL, NILAI-NILAI SOSIAL, LINGKUNGAN KERJA, PERSONALITAS PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK - Ambari, Indah Putri; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
The research was conducted to determine the effect of influence of labor market considerations, professional recognition, social values, work environment and perceptions of personality on career choice of students majoring in accounting as a public accountant in the extension program FEB Udayana. The population in this study were students from the Department of Accounting Program extensions FEB Udayana 2013. The method of determining the sample in this study using purposive sampling technique with students majoring in accounting criteria force in 2013 interested in becoming a public accountant. Data collection method used is the questionnaire method in the form of a questionnaire. Data analysis technique used is the classical assumption test, descriptive analysis and multiple linear regression analysis. The results showed that the consideration of the labor market, professional recognition, social values, work environment and personality positive and significant impact on the selection of a career as a public accountant.
Keywords: Labour Market Considerations, Professional Recognition, Social Values, Work Environment, Personality, Career As A Selection of Certified Public Accountants